THE DISSOLUTION OF THE ISLAMIC DEFENDERS FRONT ORGANIZATION AND THE REPRESENTATION OF MODERATE GROUPS IN THE DYNAMICS OF ISLAM IN INDONESIA - Imam Fawaid; Kunawi, Kunawi (Islamuna: Jurnal Studi Islam, 2025)
ABSTRACT In recent years, Indonesia has been confronted with socio-religious problems, with the discourse of Moderate Islam and Extreme Islam at stake. Because these two groups have fought over the meaning of Islam in the middle of the public space by carrying different Islamic symbols by claiming their respective truths, this has triggered horizontal conflicts based on religion. This phenomenon cannot be separated from the existence of FPI which has attracted a lot of attention among the wider community, both academics and the general public. This research aims; first, to construct the identity of FPI, second, the concept of religious derivation adopted by FPI religious organization, and, third, the dissolution of FPI. The method used is discourse analysis based on Michel Foucault's genealogy of power perspective and through a descriptive qualitative approach based on literature study sources. Data in the form of text that can be obtained from scientific literature; in the form of journals, theses, theses, visual-video and other supporting documents. The results show that the dissolution of FPI is inseparable from the power relations of moderate ulama' and the government, the findings show that FPI is an embodiment of an organizational movement that tends to be extreme in religious practice. The theoretical implication in this research is as an effort to develop the study of the role of ulama and umara' in the socio-religious context. ABSTRAK Beberapa tahun terakhir Indonesia dihadapkan pada problem sosial keagamaan, diskursus Islam Moderat dan Islam Ekstrem menjadi taruhannya. Karena kedua kelompok ini telah berebut makna Islam di tengah ruang public dengan mengusung simbol-simbol Islam yang berbeda-beda dan mengklaim kebenaran mereka masing-masing. Hal tersebut memicu terjadinya konflik horizontal yang berbasis pada agama. Fenomena demikian tidak lepas dari keberadaan FPI yang banyak menyita perhatian di kalangan masyarakat luas baik kalangan akdemik maupun masyarakat umum. Penelitian ini bertujuan; pertama, mengkonstruksi identitas FPI, kedua, konsep derivasi keagamaan yang dianut organisasi keagamaan FPI, dan, ketiga, yakni pembubaran FPI. Metode yang digunakan adalah pendekatan kualitatif deskriptif berdasarkan sumber studi pustaka dan analisis wacana berdasarkan persepektif genealogi kekuasaan Michel Foucault. Data berupa teks yang diperoleh dari literatur ilmiah, seperti jurnal, tesis, skripsi, visual-video dan dokumen pendukung lainnya. Hasil penelitian menunjukkan pembubaran FPI tidak terlepas dari relasi kuasa ulama’ moderat dan pemerintah. Berdasarkan temuan tersebut menunjukkan bahwa FPI merupakan perwujudan dari gerakan organisasi yang cenderung ekstrem dalam pengamalan keagamaan. Implikasi teoritik dalam penelitian ini adalah sebagai upaya pengembangan kajian peran ulama dan umara’ dalam konteks sosial-keagamaan.